THE PEDAGOGICAL LEGACY OF ANTON MAKARENKO: A SOVIET APPROACH TO EDUCATION AND CHARACTER - Olimov Avazbek Nurali o‘g‘li (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
This article explores the pedagogical contributions of Anton Makarenko, a prominent Soviet educator who emphasized collective upbringing, labor-based education, and moral character formation. In the wake of the Russian Revolution, Makarenko developed an educational model aimed at transforming neglected and delinquent children into responsible and productive citizens. His methods, rooted in discipline and respect, included principles such as collective responsibility, productive labor, and future-oriented goals. The article examines the core principles of his pedagogy, its practical application in educational communes, and its relevance to modern educational psychology. It concludes by suggesting ways in which Makarenko’s legacy can inform current practices in character-based and values-driven education.